Implementation of Article 90 of Kuhap in Connection Cases Based on Presidential Regulation Number 15 of 2021 About the Working Procedure Organization - Yusep Mulyana (Syntax Corporation Indonesia, 2021)
Presidential Regulation (Perpres) Number 15 of 2021 concerning the Organization and Work Procedure of the Prosecutor's Office of the Republic of Indonesia, revising Presidential Regulation Number 38 of 2010. The existence of this Perpres, attorney General's Office(AGO) officially has a Deputy Attorney General for Military Crimes. The Deputy Attorney General for Military Crimes has the duty and authority to carry out the duties and authorities of the Prosecutor's Office in the field of technical coordination of prosecutions carried out by the prosecutor and handling connectivity cases. In addition, the Deputy Attorney General for Military Crimes is also tasked with and authorized in conducting investigations of connectivity cases, researching the results of investigations, additional examinations, giving legal opinions to case handing officers, handing over cases, closing cases, stopping prosecutions, prosecutions, resistance, legal remedies, implementation of judge's determinations and court decisions that have obtained permanent legal force, examination, carrying out supervision of the implementation of conditional criminal decisions to supervisory criminal decisions, conditional release decisions